Strategy for improving teacher pedagogic competence through ummi method certification at SD Islam Al Alifah Palembang - Mirzuandi, Ahmad; Abdurrahmansyah, Abdurrahmansyah; Nazaruddin, Nazaruddin (Journal of Research in Instructional, 2024)
In modern times, many teachers still have not fully met the criteria of qualified professional teachers, especially in the Qur'an learning method with the Ummi method. This study aims to analyze the concept of increasing pedagogic competence through Ummi method certification. This research uses a qualitative approach with a case study type. The research informants were the principal, the Quran coordinator, and the Ummi method Quran teacher. The results of this study show that the concept of pedagogical competence of Qur'an teachers in the learning process is quite good, namely: 1) mastery of learning theories and learning principles by exploring each learning material conceptually through the Ummi Method volume book and literature on their respective disciplines (children's volume level); 2) curriculum development; and 3) development of student potential. The Ummi method has touched on several indicators so that the goals of Qur'an education can be achieved properly. The impact of Ummi method certification can be felt directly, not only by teachers but also by students and guardians. In the strategy to increase teacher pedagogic competence, there are four factors: strengths, opportunities, obstacles, and threats.